PARAGRAF ARGUMENTASI DALAM BAHASA JAWA (Argumentative Paragraph in Javanese Language) - Herawati Herawati (Balai Bahasa Sulawesi Selatan, 2014)
Aim of this research is to describe argumentative paragraph elements and to describe meaning relation of argumentative paragraph interelement. In data analysis step, agih method is used, a method that uses definite element as language element in its implementation. Agih method is conducted by using bagi unsur langsung (BUL) technique. Paragraph as data is divided based on its elements. Those elements are manifested as sentences, clauses, and phrases. In the discussion, it finds out that argumentation paragraph structure consists of: (1) topic sentence – explanatory sentence; (2) topic sentence-explanatory sentence-definite sentence; (3) transition-topic sentense-explanatory sentence; (4) transition-topic sentence-explanatory sentence-definite sentence.